Operational matrix approach for the solution of partial integro-differential equation - Singh S.; Patel V.K.; Singh V.K. (My University, 2025)
In this paper, an effective numerical method is introduced for the treatment of Volterra singular partial integro-differential equations. They are based on the operational and almost operational matrix of integration and differentiation of 2D shifted Legendre polynomials. The methods convert the singular partial integro-differential equation in to a system of algebraic equations. Convergence analysis and error estimates are derived for the proposed method. Illustrative examples are included to demonstrate the validity and applicability of the technique. © 2016 Elsevier Inc. All rights reserved.